Recognizing Intellectual Capital in the Intangible Asset Structure of Enterprises in the Integration Period - Nga, Nguyen Hong (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Value theory is one of the fundamental problems of economics which is applied in many different disciplines. However, the application of this economic theory in recognizing the valuation of intellectual capital of enterprises is a complex issue, especially knowledge is considered as an important form of resource and exchanged on the market. According to modern accounting theories, the accounting of intellectual capital is associated with the use of a measure of value to recognize, measure, and report on intangible assets of enterprises. However, current accounting practices do not meet the information demand of enterprise knowledge resources. This article focuses on clarifying the theoretical issues of knowledge resources in enterprises and the current state of accounting of intellectual resources in particular and intangible assets accounting in general in Vietnam in the integration period. Based on the research on content, requirements for managing knowledge resources and accounting methods, this article provides the guiding principles for the development of the accounting of intangible assets to exploit the enterprise's knowledge resources. Keywords Intellectual capital, value theory, intangible assets, enterprises References [1]. Abeysekera, I., (2003), “Intellectual accounting scorecard - Measuring and reporting Intellectual Captital”,http://ro.uow.edu.au/cgi/viewcontent.cgi?article=1590&context=commpapers [Accessed 5 June 2017] [2]. Brennan, N. và Connell, B. (2000), “Intellectual capital: current isues and policy applications”, Intellectual Capital, 1 (3), 206-240. [3]. Đặng, Đ. S., Mariott, D. N. và Mariott, P. (2006) “Qualitative insights into the provision of financial information by small and medium companies in the transitional economy of Viet nam”. The International Conference on Accounting and Finance in Trasition, April 10-12, University of South Australia, Adelaide, Australia. [4]. Guthrie, J. và Petty, R. (2000), “Intellectual capital review: measurement, reporting and management”, Journal of Intellectual Capital, 1 (1), 155-176. [5]. Ismail, T.H., (2008), “Intellectual Capital Reporting in Knowledge Economy: Evidence from Egypt [pdf]”, Available at: <http://www.cba.edu.kw/wtou/download/conf3/tariq.PDF> [Accessed 12 June 2017] [6]. Johanson, U. (1999), “Mobilising change: characteristics of intangibles proposed by 11 Swedish firms”, the International Symposium Measuring and Reporting Intellectual Capital: Experiences, Issues, and Prospects, OECD, Amsterdam, June. [7]. Moolman, S., (2010), “Intellectual Capital : Measurement, recognition and reporting, Masters of commerce in the subject Accounting, University of South Africa [pdf]”, Available at: <http://uir.unisa.ac.za/bitstream/handle/10500/4847/dissertation_moolman_s.pdf?sequence=1> [Accessed 12 June 2017] [8]. OECD (1999), “Measuring and reporting intellectual capital”, OECD Research Papers, Amsterdam. [9]. Roos, J. Roos, G. Draggonetti, N.C. và Edvinsson, I. (1997), Intellectual Capital, Macmillan Business, London. [10]. Sujan, A. and Abeysekera, I., (2007), “Intellectual capital reporting practices of the top Australian firms”, <http://ro.uow.edu.au/cgi/viewcontent.cgi?article=1437&context=commpapers [Accessed 12 June 2017].